Epigallocatechin-3-gallate activates Nrf2/HO-1 signaling pathway in cisplatin-induced nephrotoxicity in rats - Şahin, Kazım; Tuzcu, Mehmet; Gencoglu, Hasan; Dogukan, Ayhan; Timurkan, Mustafa; Şahin, Nurhan; Küçük, Ömer (Pergamon-Elsevier Science Ltd, 2010)
Aims: Cisplatin-induced nephrotoxicity is associated with increased oxidative stress and inflammatory cytokines in the kidney. Epigallocatechin-3-gallate (EGCG) has anti-oxidant, anti-inflammatory, and anti-tumorigenic properties. In this study, we investigated the effects of EGCG on cisplatin-induced nephrotoxicity and potential mechanisms by which it enhances antioxidant activities and resolves inflammation after EGCG treatment during cisplatin-induced nephrotoxicity. Main methods: Twenty-eight rats were divided into four groups as control (group 1; no treatment; n = 7), EGCG (group 2; n = 7), cisplatin (group 3; n = 7) or cisplatin and EGCG (group 4; n = 7). After 2 days of EGCG treatment at a dose of 100 mg/kg BW, rats were treated with a single i.p. injection of cisplatin (7 mg/kg BW). On day 12 (10 days after the cisplatin treatment), all rats were sacrificed by cervical dislocation. The level of protein was examined by Western blotting. Key findings: Cisplatin caused a significant decrease in the expression nuclear levels of NF-E2-related factor-2 (Nrf2), heme oxygenase-1(HO-1), and an increase in the levels of nuclear factor-kappa B (NF-kappa B p65) and 4-hydroxynonenal (HNE) an oxidative stress marker. EGCG supplementation significantly improved the changes associated with cisplatin nephrotoxicity by increasing levels of Nrf-2 and HO-1, and decreasing levels of NF-kappa B and HNE. Renal activities of antioxidant enzymes (catalase, superoxide dismutase, glutathione peroxidase) and glutathione were significantly lower in cisplatin-treated rats compared with control rats, and EGCG treatment significantly increased the activities of antioxidant enzymes and glutathione (P<0.001). Significance: The results suggest that Nrf2/HO-1 signaling pathway may be the primary target for prevention of cisplatin-induced nephrotoxicity by EGCG, and that reduces it inflammation by inhibiting NF-kappa B. (c) 2010 Elsevier Inc. All rights reserved.
Keywords: Epigallocatechin-3-gallate; Nrf2; HO-1; Cisplatin; Nephrotoxicity